XOTEMENTE: IT IS FROM XOTE TO XOTE THAT THE MIND GROWS STRONG (Editora Impacto Científico, 2025)
Going through the pages of this ebook is to discover that forró is much more than just choreographed steps. It's a complete journey of self-discovery and connection. We discuss everything from the benefits for physical and mental health to promoting increased affection and circles of support and friendship. We delve into the chemistry of happiness, understanding how dance is a powerhouse of endorphins, serotonin, dopamine, and oxytocin, reducing cortisol and stress. By reading this book, take to the dance floor and to life the certainty that each forró step is a step towards a happier, healthier, and more connected version of yourself. Embrace the dance. Embrace life.DOI: https://doi.org/10.56238/edimpacto2025.090-077